Redução da pressão arterial ambulatorial após uma sessão de treinamento de corrida na intensidade do limiar anaeróbio em corredores de meia idade - Pezzim, Juliana Zanol Cardoso (2017)
Street racing is a sporting practice that grows every year around the world, as well as its number of fans, and many of these runners start this activity in middle age, seeking physical, social and psychological benefits. Continuous aerobic exercise, a nonpharmacological instrument for controlling blood pressure (BP), and most related to postexercise hypotension, was the objective of this study to describe the cardiovascular responses of heart rate (HR) recovery and blood pressure (PB), recorded during the 24 hours following a training session in the intensity of the ventilatory anaerobic threshold (LAV) of healthy middle-aged runners, compare the mean and 24-hour heart rates, wakefulness, sleep and pressure loads in the same Periods between ABPM control and ABPM after the LAV session, and also to compare the hourly mean blood pressure and HR of the ABPM and ABPM after the LAV session in the wake and sleep periods. Twenty-two healthy middle-aged men, runners, underwent an exercise session performed on LAV intensity, and BP was measured by ABPM after the session and was compared to ABPM performed on a control day. Mean SBP presented a reduction in 24h (123 ± 2 vs. 120 ± 2, p≤0.009) and in the Vigil (127 ± 2 vs. 123 ± 2, p≤0.002) ; mean values of PAD showed reduction in 24h (73 ± 1 vs 74 ± 2, p≤0.019), in the wake period (80 ± 1 vs 78 ± 2, p≤0.020). The mean MAP was also reduced in 24h (91 ± 1 vs 89 ± 2, p <0.004) and in wakefulness (95 ± 1 vs 93 ± 2, p≤0.016). The systolic pressure load values showed a significant reduction in the mean of 24h (p <0.005) and in mean waking (p <0.003); (P <0.032) and the mean of sleep (p <0.015). The behavioral curve of the HR and FC hours showed a significant reduction of SBP (p <0.004), DBP (p <0.031), MAP (p <0.017) between moments (control x LAV). In conclusion, an aerobic exercise session performed in the LAV intensity causes a reduction in systolic, diastolic and mean ambulatory blood pressure in healthy middle-aged street runners in the wake and 24 hours, but not in sleep.